Loving Our Clients: Can We Share All The Fruits? (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
How can therapists love clients ethically? Kierkegaard, Plato and other philosophers suggest some forms of love are better than others. I argue that elevating a chosen agape over a given eros is ontologically confused. All forms of loving our clients reveal something helpful, and ethically we can be aware and beware.
Keywords: Love; ethics; Kierkegaard; Plato; agape; eros; choice; emotion